Sequência didática de calorimetria com foco no ciclo hidrológico para o ensino de Física no Ensino Médio - BEZERRA, Rosa Leonor Bentes Souza (2023)
Physics is considered a great challenge by students, so it is important to compose methodological strategies that provide students with an approach to the world of Physics. This work presents a didactic sequence elaborated for teaching concepts of calorimetry. The didactic sequence, which is based on the study of calorimetry with a focus on the Hydrological Cycle, was structured for students in the second year of high school, for Physics classes, aiming at raising awareness and conservation of natural resources, as well as bringing improvement for education and interaction between teacher and student, and between students and other colleagues and their environment. The study aimed to propose a didactic sequence seeking an interdisciplinary teaching based on socio-environmental problems in the context of the hydrological cycle, heat and temperature for Physics classes, allowing this student to understand the world around him and the physical phenomena that surround him. The study was based on bibliographical research in academic articles, books and websites that bring a study on the theme of the water cycle.